1990
DOI: 10.1002/eji.1830200334
|View full text |Cite
|
Sign up to set email alerts
|

Lymphokines and bacteria, that induce tumoricidal activity, trigger a different secretory response in macrophages

Abstract: The abilities of various macrophage-activating agents to trigger tumoricidal activity and/or the secretion of prostaglandin E2 (PGE2), interleukin 6 (IL 6) and transforming growth factor beta (TGF beta) in bone marrow-derived mononuclear phagocytes (BMM phi) in vitro were comparatively assessed. Induction of tumoricidal activity by lymphokines, that is only short-lived, was not associated with enhanced secretion of these activities by BMM phi; in contrast, incubation with heat-killed facultative intracellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
2

Year Published

1991
1991
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 26 publications
0
30
0
2
Order By: Relevance
“…Thus, lymphokine-triggered cytotoxic activity in bone marrow-derived phagocytes declines after 24 h, but that elicited by bacteria persists (Keller et al, 1990). Furthermore, the secretion of IL-6 and prostaglandin E2 (PGE2) is enhanced by bacteria but not by lymphokines.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, lymphokine-triggered cytotoxic activity in bone marrow-derived phagocytes declines after 24 h, but that elicited by bacteria persists (Keller et al, 1990). Furthermore, the secretion of IL-6 and prostaglandin E2 (PGE2) is enhanced by bacteria but not by lymphokines.…”
Section: Discussionmentioning
confidence: 99%
“…Peritoneal macrophages can be stimulated by a variety of agents such as IFN-γ, lipopolysaccharides, or other microbial products [17][18][19] and some of these have also been shown to trigger the release of TNF-α, IL-1β and IL-6 by the macrophages [20][21][22][23]. Peritoneal macrophages proliferation result showed that from 100 µg/mL to 300 µg/mL, TCDCA appeared markedly progressing inhibition, and its inhibited rates reached to 10%, 20% and 30% in the concentration of TCDCA 150 µg/mL, 180 µg/mLand 200 µg/mL, respectively (Figure 3).…”
Section: Effects Of Tcdca On Expression Of Iκbα and Phospho-iκbαmentioning
confidence: 99%
“…NO, one of the smallest biological molecular mediators plays important roles in many different aspects of mammalian biology, such as vascular relaxation, neurotransmission, platelet aggregation and immune regulation (Hemmi and Ishida, 1980;Hibbs et al, 1988). Since NO is related to cytostatic or cytotoxic function of macrophages against a variety of tumors (Hibbs et al, 1987;Keller et al, 1990), we examined the effects of EBE on the NO production from macrophages in exercise-stress rats. It is known that iNOS is expressed in many different cell types and produces high levels of NO.…”
Section: Resultsmentioning
confidence: 99%